ОЦЕНКА ТЕХНОЛОГИЧЕСКОЙ СОСТАВЛЯЮЩЕЙ НЕФТЯНОЙ ПРОМЫШЛЕННОСТИ КАЗАХСТАНА - Бордоусов, О В (Journal of Economic Research & Business Administration, 2015)
The analysis of indicators of the mining industry is reported in this article. The estimation of expenses of factors of manufacture and scientific and technical progress is made.